Analisis Perbaikan Kualitas Menggunakan Metode Failure Mode Effect And Analysis (FMEA) Dan Fault Tree Analysis (FTA) Untuk Mengurangi Tingkat Kecacatan Produk Titanium Frit di PT. Sicer Indonesia - Sarwoko, Wanto (Universitas Pamulang, 2023)
PT Sicer Indonesia is a ceramic manufacturer company which is produce various types of products such as Glaze, Engobe and Medium. Observations were made on the Titanium Frit (Glaze) production section and Quality Control results. This research aims to determine the factors that cause defects in products, determine corrective actions and reduce the number of product defects. Defects that often occur in Titanium Frit are Less White, Pinhole, Blackspot and Yellowish. Where the largest percentage of defects was in February at 43.2%. Therefore, effective quality control efforts are needed. In this research, the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods were used to identify and analyze defects that occurred. FMEA is used to determine and multiply the severity level, occurrence level and detection level, to obtain a Risk Priority Number (RPN) value which can determine the priority of defects that must be prioritized for repair. The highest RPN defect value is the Pinhole defect with RPN 448.. FTA is used to find out the root cause of the defect that occurs. The main factors causing defects in the Titanium Frit production process consist of 4 factors, human factors are caused by workers who do not work according to SOP, lack of machine maintenance, unstable material quality, and environmental contamination. The results or quality improvement actions taken are carrying out consistent supervision to ensure that workers have worked according to the SOP and carrying out maintenance on materials and machines as a whole regularly before use.